Urinary incontinence in postmenopausal women in the aspect of sexual health and therapeutic approach - Ziarnik, Kacper; Nadolny, Filip; Jabłoński, Jędrzej; Kania, Martyna; Adamowska, Agnieszka; Śniatała, Alicja; Bartkowiak, Hanna; Grubski, Damian (Journal of Education, Health and Sport, 2024)
Introduction Urinary incontinence (UI) is a prevalent condition among postmenopausal women, seriously impacting their sexual health and quality of life. In the postmenopausal period, multiple hormonal and structural changes occur in female body. These conditions can lead to psychosomatic disorders, causing shame, social withdrawal, and negatively affecting sexual health. Loss of bladder control creates discomfort during sex, reducing satisfaction for both women and their partners. Management strategies for UI in postmenopausal women include pelvic floor training, medications, and surgical options. Addressing the psychosocial aspects of urinary incontinence through counseling and education is essential for empowering women to seek support. Aim of the study The article discusses urinary incontinence in postmenopausal women, highlighting its impact on sexual health. It discusses the hormonal and physiological changes related to this condition and aims to present effective diagnostic and treatment strategies. Materials and methods We searched the following databases: PubMed, Web of Science, clinical trial registry platforms, and Google Scholar, using key terms such as "urinary incontinence," "postmenopausal women," "sexual health," "lower urinary tract symptoms (LUTS).” Conclusion UI is a serious problem affecting many postmenopausal women. It is crucial to elevate the understanding of both patients and medical staff about diagnosis, effective treatment options, and the importance of mental support. By taking this approach, we can create a healthcare environment that is more informed and compassionate.